Insights into the Mechanism of Action of Bactericidal Lipophosphonoxins - Panova, Natalya; Zborníková, Eva; Šimák, Ondřej; Pohl, Radek; Kolář, Milan; Bogdanová, Kateřina; Večeřová, Renata; Seydlová, Gabriela; Fišer, Radovan; Hadravová, Romana; Šanderová, Hana; Vítovská, Dragana; et al. (PloS one, 2015)
The advantages offered by established antibiotics in the treatment of infectious diseases are endangered due to the increase in the number of antibiotic-resistant bacterial strains. This leads to a need for new antibacterial compounds. Recently, we discovered a series of compounds termed lipophosphonoxins (LPPOs) that exhibit selective cytotoxicity towards Gram-positive bacteria that include pathogens and resistant strains. For further development of these compounds, it was necessary to identify the mechanism of their action and characterize their interaction with eukaryotic cells/organisms in more detail. Here, we show that at their bactericidal concentrations LPPOs localize to the plasmatic membrane in bacteria but not in eukaryotes. In an in vitro system we demonstrate that LPPOs create pores in the membrane. This provides an explanation of their action in vivo where they cause serious damage of the cellular membrane, efflux of the cytosol, and cell disintegration. Further, we show that (i) LPPOs are not genotoxic as determined by the Ames test, (ii) do not cross a monolayer of Caco-2 cells, suggesting they are unable of transepithelial transport, (iii) are well tolerated by living mice when administered orally but not peritoneally, and (iv) are stable at low pH, indicating they could survive the acidic environment in the stomach. Finally, using one of the most potent LPPOs, we attempted and failed to select resistant strains against this compound while we were able to readily select resistant strains against a known antibiotic, rifampicin. In summary, LPPOs represent a new class of compounds with a potential for development as antibacterial agents for topical applications and perhaps also for treatment of gastrointestinal infections.
Keywords: Protein Binding; Bacillus subtilis; Male; aktivní transport; pyrimidinové nukleosidy; Pyrimidine Nucleosides; molekulární struktura; antibakteriální látky; Molecular Structure; Microbial Sensitivity Tests; mužské pohlaví; Drug Stability; grampozitivní bakterie; Cell Membrane Permeability; Biological Transport, Active; permeabilita buněčné membrány; Mice, Inbred ICR; Streptococcus agalactiae; vazba proteinů; Cell Membrane; Animals; lidé; objevování léků; ženské pohlaví; stabilita léku; Anti-Bacterial Agents; Gram-Positive Bacteria; Humans; Caco-2 Cells; zvířata; Microscopy, Electron, Transmission; mikrobiální testy citlivosti; buněčná membrána; myši; Caco-2 buňky; myši inbrední ICR; Drug Discovery; Enterococcus faecalis; Mice; Female; transmisní elektronová mikroskopie